Zero Trust Security Architecture for Legacy Systems - Vasanth Kumar Naik Mudavatu (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The integration of Zero Trust Architecture (ZTA) with legacy systems presents a critical security challenge for modern organizations. This comprehensive article explores how the "never trust, always verify" principles of ZTA can be effectively implemented to protect vulnerable legacy infrastructure without necessitating complete system replacement. The article examines the fundamental shift from traditional perimeter-based security models to a more robust approach that treats all access requests as potentially malicious regardless of origin. Through detailed examination of key ZTA components—identity-centric security, micro-segmentation, and continuous monitoring—the article provides a pragmatic implementation strategy specifically tailored for legacy environments. It addresses common implementation challenges such as limited API support, hardcoded credentials, and protocol limitations, offering practical mitigation strategies for each. A real-world application example featuring a financial institution with mainframe-based core banking systems demonstrates how these principles can be applied in high-stakes environments. It concludes that despite implementation complexities, the security benefits of ZTA for legacy systems substantially outweigh the challenges, enabling organizations to extend the secure operational lifespan of critical legacy infrastructure.